Parenting support in Portugal - Sarmento, Teresa (Advances in Social Sciences Research Journal, 2016)
The family, in Portugal, is experienced as a core value, which holds almost exclusive responsibility for the education of young children.  This paper presents some indicators that help to understand the situation of families in Portugal, with particular focus on their educational conditions. Alongside this, I mean the state's role in supporting educational family obligations, analyzing how this, along with civil society, promotes suport parental actions. In this sense they are described some specific programs, especially developed with families at risk, and that allow us to know what is being done on the ground. The text ends with the raising of a set of comments and considerations to attend to promote the improvement of parental support programs